Explanation of the problems of the health sector budgeting process in the Islamic Republic of Iran - Mostsfa Samiee Nasab; elyas hadian shiva; Mohammad Azadi Ahmadabadi (Payesh)
Objective(s): Considering that the government directly provides a significant part of the health system's resources and provides a significant part of the health goods and services, and is indirectly the channelizer of the private sector and its resources, one of the ways to improve the health system is to reform the health budgeting process.  The budgeting process consists of four stages of formulation, approval, implementation and monitoring, which are discussed in this article. Methods: In this descriptive study, after reviewing the existing literature, data were obtained through 11 semi-structured interviews with health system experts. The interviews were transcribed entered into MaxQuda software. Thematic approach was used to analyze the data. Results: 400 codes were identified, and after several stages of screening, 310 codes remained. Health budget formulation issues were categorized into 18 themes. The most important issues in the compilation section were in terms of the number of repetitions of the codes related to the organizing themes of "budget amount and distribution", "policies and priorities", "program organization" and "systems and transparency". Conclusion: Part of health budget formulation issues, such as the instability of resources and low incomes, are rooted in the macroeconomic situation of the country, which is out of the health system’s control. Regardless of the amount of the health budget and its distribution method, the lack of a macro strategy and the lack of connection between the budget and the upstream documents and development plans, the inefficiency of the program organization structure, and the lack of information and registration systems are some of the most important issues that have affected the budget formulation process.